A Comparison of the Effectiveness of Cyberlegislation in Malaysia and the UK: A Case Study of Computer Crimes Act 1997 and Digital Signature Act 1997 - Osman, Lama (2008)
The research\'s main objective is to analyze two pieces of Malaysian legislation, the Digital Signature Act 1997, and the Computer Crimes Act, 1997.